1939
DOI: 10.1113/jphysiol.1939.sp003721
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory effect of acetylcholine on water diuresis in the dog, and its pituitary transmission

Abstract: RECENT work has made it appear possible that acetylcholine is the effective transmitter of impulses in the central as well as in certain distributions of the peripheral nervous system. Dikshit's work [1934, 1935] first brought this idea into the realm of probability. He injected acetylcholine into the hypothalamus and ventricles of cats and found that the effects produced were similar to those of electrical stimulation of those parts. Later, Chang, Chia, Hsi! & Lim [1937] showed that a reflex secretion of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1

Year Published

1940
1940
2000
2000

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(26 citation statements)
references
References 5 publications
0
25
1
Order By: Relevance
“…sample in these experiments resulted from the acetylcholine injection. The lack of efficacy of a comparatively high dose of acetylcholine may have been caused by a failure of the acetylcholine to reach the acetylcholine-sensitive areas in the central nervous system (probably in the supraoptic and paraventricular nuclei) activation of which can release ADH (Pickford, 1939(Pickford, , 1947Duke & Pickford, 1951). If so, this could have been the result of anatomical differences in the blood supply of the brain between the rat and the dog because Pickford and her colleagues used dogs.…”
Section: Effect Of Haemorrhage On the Blood Concentration Of Vasopressinmentioning
confidence: 99%
See 1 more Smart Citation
“…sample in these experiments resulted from the acetylcholine injection. The lack of efficacy of a comparatively high dose of acetylcholine may have been caused by a failure of the acetylcholine to reach the acetylcholine-sensitive areas in the central nervous system (probably in the supraoptic and paraventricular nuclei) activation of which can release ADH (Pickford, 1939(Pickford, , 1947Duke & Pickford, 1951). If so, this could have been the result of anatomical differences in the blood supply of the brain between the rat and the dog because Pickford and her colleagues used dogs.…”
Section: Effect Of Haemorrhage On the Blood Concentration Of Vasopressinmentioning
confidence: 99%
“…The use of atropine has the additional advantage that it prevents the formation of tracheal and bronchial exudate which occurs when ether is used as an anaesthetic. It has been shown by several workers that atropine does not prevent the release of vasopressin (Pickford, 1939;Fang, Liu & Wang, 1962;Mills & Wang, 1964b) although de Wied & Laszlo (1967) All blood samples were taken through polythene cannulae into polythene tubes and injected into the assay animals with plastic syringes to prevent the formation of interfering substances which can occur if blood is stored in glass containers (Bisset & Walker, 1957). Assays of the activity of whole blood samples were started immediately after collection and a four point assay could be completed in about 1 hr.…”
mentioning
confidence: 99%
“…The site of this vasopressin releasing action of nicotine has not been subject to controversy until quite recently. Pickford (1939) demonstrated that acetylcholine induces an antidiuretic response in atropinized dogs and that this response is absent in animals with experimental diabetes insipidus. Subsequently Pickford (1947) and Duke, Pickford & Watt (1950) showed that the neurones in the supraoptic nucleus exhibit nicotinic-like receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Many stimuli, in addition to hypertonicity, increase ADH production, including certain anaesthetic (1) and narcotic drugs (2), barbiturates (3), smoking (4,5) and nicotine (6, 7), acetylcholine (8), exercise (9), emotion (9), syncope ( 10), pain ( 11 ) and conditioned reflexes ( 11 ), as well as the direct electrical (12) or acetylcholine (13) stimulation of nerve cells and fibers connected with the pars nervosa of the pituitary gland. Removal of amounts of blood insufficient to alter blood pressure significantly may nevertheless lead to increased ADH activity (9).…”
mentioning
confidence: 99%